1986
DOI: 10.1126/science.3016895
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Pathways of Viral Spread in the Host Determined by Reovirus S1 Gene Segment

Abstract: The genetic and molecular mechanisms that determine the capacity of a virus to utilize distinct pathways of spread in an infected host were examined by using reoviruses. Both reovirus type 1 and reovirus type 3 spread to the spinal cord following inoculation into the hindlimb or forelimb footpad of newborn mice. For type 3 this spread is through nerves and occurs via the microtubule-associated system of fast axonal transport. By contrast, type 1 spreads to the spinal cord through the bloodstream. With the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
199
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(203 citation statements)
references
References 37 publications
3
199
1
Order By: Relevance
“…Infection with various strains of the virus have been shown to cause a variety of conditions including hepatitis, lymphoma, pancreatitis, necrotizing encephalitis, and myocarditis. [23][24][25][26][27] However, the development of distal extremity necrosis has not been previously characterized in association with reovirus infection in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with various strains of the virus have been shown to cause a variety of conditions including hepatitis, lymphoma, pancreatitis, necrotizing encephalitis, and myocarditis. [23][24][25][26][27] However, the development of distal extremity necrosis has not been previously characterized in association with reovirus infection in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of viral transport in the nervous system has mainly focused on in vivo studies. It has been postulated that neurotropic viruses are transported via nerve tracts into the nervous system (Bak et al, 1977;Carbone et al, 1987;Dal Canto et al, 1986;Gillet et al, 1986;Kaluza et al, 1987;Kimberlin & Walker, 1986;Klein & DeStefano, 1983;Kucera et al, 1985;Tyler et al, 1987). However in most of these observations, the possibility that other cell types or that other mechanisms may be involved in addition to the specific neural transport has not been totally discarded.…”
Section: Introductionmentioning
confidence: 88%
“…Previous studies have shown that neurotropic viruses can initiate infection in the periphery and can move through peripheral neurons to reach the central nervous system (Card et al, 1991;Ohka et al, 1998;Samuel et al, 2007;Tyler et al, 1986). Therefore, we hypothesized that mice with neurotropic disease may have higher viral titres in peripheral neurons and brain.…”
Section: Yfv-17d Titres In Ifnar "/" Micementioning
confidence: 97%